Substituent‐induced deformed ni–porphyrin as an electrocatalyst for the electrochemical conversion of water into dioxygen - Krishna, J. V. S.; Krishna, Narra Vamsi; Singh, Santosh K.; Shaw, Pankaj K.; Dhavale, Vishal M.; Vardhaman, Anil Kumar; Giribabu, Lingamallu (European Journal of Inorganic Chemistry, 2018)
The electrochemical water oxidation ability of complexes 5,15‐diphenylporphinatonickel(II) (A) and 5,15‐bis(3,5‐di‐tert‐butylphenyl)porphinatonickel(II) (B) in the oxygen evolution reaction (OER) have been investigated in an alkaline medium. Complex B was found to be kinetically and thermodynamically more active than complex A. The overpotential and Tafel slope of complex B are lower than those of complex A by 30 mV and around 45 mV/decade, respectively, which supports the higher activity of B. Moreover, stability tests endorse the sustainability of both samples under alkaline conditions. It has been found that the 3,5‐di‐tert‐butylphenyl substituent in B plays a decisive role in achieving a better OER onset potential and current than that obtained with A, which is a result of the modulation of the structural parameters of B. Furthermore, the measured OER activities of A and B have been correlated with their molecular arrangement as well as differences in their bonding characteristics and dipole moments. For further insight, the obtained results have been confirmed by a theoretical study.